2007
DOI: 10.1038/ng2039
|View full text |Cite
|
Sign up to set email alerts
|

The ciliary gene RPGRIP1L is mutated in cerebello-oculo-renal syndrome (Joubert syndrome type B) and Meckel syndrome

Abstract: Cerebello-oculo-renal syndrome (CORS), also called Joubert syndrome type B, and Meckel (MKS) syndrome belong to the group of developmental autosomal recessive disorders that are associated with primary cilium dysfunction. Using SNP mapping, we identified missense and truncating mutations in RPGRIP1L (KIAA1005) in both CORS and MKS, and we show that inactivation of the mouse ortholog Rpgrip1l (Ftm) recapitulates the cerebral, renal and hepatic defects of CORS and MKS. In addition, we show that RPGRIP1L colocali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
486
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 446 publications
(515 citation statements)
references
References 26 publications
17
486
0
Order By: Relevance
“…19 This would be in line with the observation that mild mutations in MKS-associated genes can cause JBS, for example, RPGRIP1L/MKS5 and CC2D2A/MKS6. 35,36 The patient presented with a mild classic JBS phenotype without renal, retinal, or hepatic disease (at age 10 years), similar to the phenotype of two JBS cases with B9D1 mutations described recently. 19 The percentage of JBS cases with a heterozygous mutation in a known JBS gene (53%) is much higher than expected in a rare autosomal recessive disease (the estimated birth prevalence of JBS is 1 in 80 000 to 1 in 100 000); 2,7 however, we cannot exclude that a second pathogenic mutation is present but missed by our detection method.…”
Section: Non-mendelian Inheritance and B9d1supporting
confidence: 69%
“…19 This would be in line with the observation that mild mutations in MKS-associated genes can cause JBS, for example, RPGRIP1L/MKS5 and CC2D2A/MKS6. 35,36 The patient presented with a mild classic JBS phenotype without renal, retinal, or hepatic disease (at age 10 years), similar to the phenotype of two JBS cases with B9D1 mutations described recently. 19 The percentage of JBS cases with a heterozygous mutation in a known JBS gene (53%) is much higher than expected in a rare autosomal recessive disease (the estimated birth prevalence of JBS is 1 in 80 000 to 1 in 100 000); 2,7 however, we cannot exclude that a second pathogenic mutation is present but missed by our detection method.…”
Section: Non-mendelian Inheritance and B9d1supporting
confidence: 69%
“…Despite two patients displaying an occipital encephalocele, no ARL13B variants have been found in Meckel syndrome fetuses (Cantagrel et al 9 and personal data), although Meckel syndrome has been shown to be the extreme lethal phenotype of JS for other genes. [29][30][31][32][33] In conclusion, we have identified a novel homozygous missense variant in ARL13B/JBTS8 in a JS patient with retinal involvement and obesity. We have shown that this variant is hypomorphic, as it is unable to rescue efficiently either the arl13b sco zebrafish phenotype or the deficiencies in Arl13b hnn MEFs.…”
Section: Discussionmentioning
confidence: 67%
“…These include Ableson-helper integration-1 (AHI1), Nephrocystin-1 (NPHP1), Centrosomal protein-290 (CEP290), Transmembrane protein 67 (TMEM67) and Retinitis pigmentosa GTPase regulator-interacting protein-like (RPGRIP1L). Each of the genes encodes a modular scaffolding protein without clear enzymatic domains, but sharing several protein-interaction domains of unknown function, suggesting that they may be part of a signaling complex [28][29][30][31][32][33][34][35][36] The Joubert syndrome connection with cilia Although the function of JSRD proteins remains largely unknown, recent evidence suggests roles in either mediating the assembly/stability of cilia or mediating cargo transport within cilia. When tested directly, at least three of the encoded proteins, NPHP1, CEP290 and RPGRIP1L have demonstrated localization to the basal body or cilium [32,[35][36][37], further suggesting a role at the cilium or basal body.…”
Section: Joubert Syndrome and Related Disordersmentioning
confidence: 99%